Integrating network analysis with chromatography: introducing a novel chemometry-chromatography based analytical procedure to classify the bacterial cell wall collection. Issue 10 (20th February 2018) - Kumar, Keshav; Cava, Felipe
Abstract : The present work integrates network analysis with chromatography and proposes a novel analytical procedure to classify the bacterial cell wall collection. Abstract : The present work integrates network analysis with chromatography and proposes a novel analytical procedure to classify the bacterial cell wall collection. The network analysis model can capture the heterogeneity present in the datasets and hence can provide unsupervised classification. The proposed approach is successfully applied for classifying the peptidoglycan samples of certain bacterial collections belonging to the class of Alphaproteobacteria. The obtained classification results are found to correlate well with their relative similarity in the peptidoglycan compositions. In summary, the proposed network analysis approach can be helpful in automatizing the bacterial cell wall analysis. The proposed approach can be useful to accelerate the research related to understanding the morphology of bacterial cell walls, host–pathogen interaction and development of effective antibiotics.